2012
DOI: 10.1016/j.oregeorev.2011.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in element concentration and isotope ratio analysis of individual fluid inclusions by laser ablation single and multiple collector ICP-MS

Abstract: Recent developments in element concentration and isotope ratio analysis of individual fluid inclusions by laser ablation single and multiple collector ICP-MS. Ore Geology Reviews 44, 10-38.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
176
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 248 publications
(189 citation statements)
references
References 167 publications
(243 reference statements)
2
176
1
3
Order By: Relevance
“…To avoid the incorporation of possible surface contaminants, a "cleaning" with 25 % overlap per pulse was conducted directly before and along the transect of the actual measurement. The data were processed by using the software SILLS (Guillong et al, 2008), which calculates the detection limit after Pettke et al (2012). Any exsolution lamellae of ilmenite and ulvöspinel in magnetite were incorporated into the LA-ICP-MS analyses to represent the initial composition of the Fe(-Ti) oxide (Dare et al 2014a).…”
Section: Laser Ablation Inductively Coupled Plasma Mass Spectrometry mentioning
confidence: 99%
“…To avoid the incorporation of possible surface contaminants, a "cleaning" with 25 % overlap per pulse was conducted directly before and along the transect of the actual measurement. The data were processed by using the software SILLS (Guillong et al, 2008), which calculates the detection limit after Pettke et al (2012). Any exsolution lamellae of ilmenite and ulvöspinel in magnetite were incorporated into the LA-ICP-MS analyses to represent the initial composition of the Fe(-Ti) oxide (Dare et al 2014a).…”
Section: Laser Ablation Inductively Coupled Plasma Mass Spectrometry mentioning
confidence: 99%
“…Heinrich et al [159] and Pettke et al [160] systematically reviewed the influencing factors, the calibration methods, the accuracy and the detection limits for the analysis of single melt/fluid inclusion by LA-ICP-MS. Shepherd and Chenery [161] were the first to study the feasibility of analyzing element compositions of single fluid inclusions by LA-ICP-MS. Moissette et al [162] proposed a calibration strategy for the analysis of single fluid inclusions based on the use of the synthetic fluid inclusion in halite as an external standard. Applying a simple external calibration method, Ghazi et al [163] and McCandless et al [51] analyzed the single fluid inclusions in halite and quartz calibrated against a standard solution sealed in a glass capillary.…”
Section: Individual Melt Inclusion and Fluid Inclusionmentioning
confidence: 99%
“…The total salinity was generally determined by microthermometric measurements of phase transitions from known phase diagrams via measurements of either the depression of the ice-melting temperature or the temperature of dissolution of NaCl crystals. The methods used to estimate the Na (or Cl) content by salinity may affect the analysis accuracy of single fluid inclusions [160,165]. Allan et al [166] demonstrated that precision and accuracy are insensitive to inclusion size and depth.…”
Section: Individual Melt Inclusion and Fluid Inclusionmentioning
confidence: 99%
“…Several spots were measured on each sample either on a crystal face, a polished crystal face, or a polished section. A detailed description of the experimental setup and parameters is given in Pettke et al (2012). Measurements were performed with a beam diameter of 90 µm, and SRM610 was used as the external standard material.…”
Section: Chemical Analysismentioning
confidence: 99%